ผลของเศษฝุ่นที่นำกลับมาใช้เป็นสารตัวเติมต่อสมบัติของผ้าเบรก - กนกวรรณ ชนะดัสกร (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
This research is focused on the effect of recycling dust (RD) on properties and performance of disc brake pad composite. Three different types of recycling dust, low steel dust (LSD), low copper dust (LCD) and non-copper dust (NCD), were characterized by sieve analysis. X-ray fluorescent (XRF) and scanning electron microscopy (SEM). The results found that the particle size distribution of recycling dust with board size range is smaller than 71 microns with irregular in shape. The presence of elements in different recycling dust is almost the same except metal composition including copper and steel fibers which LSD gives the highest amount around 5.15 wt.%. Then, the influence of the various type of recycling dust (LSD, LCD, NCD, and mixed-RD) was investigated by increasing 10 wt.% of recycling dust on commercial brake pad formulation. The results of increasing 10 wt.% of recycling dust show that the properties and performance of brake pad, specific gravity, porosity, hardness, modulus, a coefficient of friction, and specific wear rate, gradually change with slightly increased in coefficient of friction and wear rate compared with the commercial brake pad. Therefore, every type of recycling dust can be reused as new raw material but for the convenient way of recycling waste management, the use of mixed-RD is recommended. After that, the influence of the amount of recycling dust, 5%, 10%, 15%, 20% and 25% by weight, was investigated. The results show that hardness, compressibility, and modulus are barely changed while the specific gravity decreases. The sample with 25% of recycling dust has the highest level of wear rate around 1.85x10-7 cm3/N.m while others have a range of 1.65x10-7-1.66x10-7 cm3/N.m. Moreover, the sample with 20% of recycling dust has the highest friction stability and can reduce the cost of raw material around 2.4 million baht per years.